Security, Uncertainty, and Urban Futures: A Conversation with Austin Zeiderman - Müller, Frank (Critical Reviews on Latin American Research - CROLAR, 2021)
How has the opposition between “civilized” urbanity and “barbaric” rurality conditioned future imaginaries in Latin America? What are the historical links between urbanization and attempts to establish social and spatial order during colonization, after independence, and in other political conjunctures? In the following conversation, anthropologist Austin Zeiderman reviews historical perspectives on Latin American cities with a focus on the future. With an interest in the genealogy of urban imaginaries, he sheds light on contemporary preoccupations with future uncertainty and the specific role that security plays therein. Ever since the conquistadors set foot on the continent, he argues, the future has exerted affective power via hopes, threats, and visions of both utopian and dystopian possibilities.